The Impact of Capital and Foreign Exchange Flowson the Competitiveness of Developing Countries - Kamar, Bassem (IMF Working Papers; Working Paper, 2010)
Attracting capital and foreign exchange flows is crucial for developing countries. Yet, these flows could lead to real exchange rate appreciation and may thus have detrimental effects on competitiveness, jeopardizing exports and growth. This paper investigates this dilemma by comparing the impact of six types of capital and foreign exchange flows on real exchange rate behavior in a sample of 57 developing countries covering Africa, Europe, Asia, Latin America, and the Middle East. The results reveal that portfolio investments, foreign borrowing, aid, and income lead to real exchange rate appreciation, while remittances have disparate effects across regions. Foreign direct investments have no effect on the real exchange rate, contributing to resolve the above dilemma.